Design of cost-effective environment-responsive nanoacoustic devices based on mesoporous thin films - Cardozo de Oliveira, Edson R. (2023)
Gigahertz acoustic resonators have the potential to advance data processing and quantum communication. However, they are expensive and lack responsiveness to external stimuli, limiting their use in sensing applications. In contrast, low-cost nanoscale mesoporous materials, known for their high surface-to-volume ratio, have shown promise in various applications. We recently demonstrated that mesoporous silicon dioxide (SiO2) and titanium dioxide (TiO2) thin layers can support coherent acoustic modes in the 5 to 100 GHz range. In this study, we propose a new method for designing tunable acoustic resonators using mesoporous thin films on acoustic distributed Bragg reflectors. By infiltrating the pores with different chemicals, the material´s properties could be altered and achieve tunability in the acoustic resonances. We present four device designs and use simulations to predict resonators with Q-factors up to 1000. We also observe that the resonant frequency and intensity show a linear response to relative humidity, with a tunability of up to 60 %. Our platform offers a unique opportunity to design cost-effective nanoacoustic sensing and reconfigurable optoacoustic nanodevices.